An inactive control of the 'Trier Social Stress Test' for Youth 10–17 years: Neuroendocrine, cardiac, and subjective responses. (June 2019) - Wu, Jia; Phillip, Tammi-Marie; Doretto, Victoria; van Noordt, Stefon; Chaplin, Tara M.; Hommer, Rebecca E.; Mayes, Linda C.; Crowley, Michael J.
Highlights: The first randomized study comparing Trier Social Stress Test for Children (TSST-C) to an inactive controll procedure among youth 10–17 years. Subjective anxiety, salivary cortisol, systolic, diastolic blood pressure rose to the stressor in the TSST-C group, but they did not increase in the inactive control group. The initial measurement of the salivary cortisol was significantly greater than the second measurement. The baseline salivary cortisol linearly increased with age, while the stress reactivity of the salivary cortisol peaked in mid-age adolescents (13–15 years old). The inactive control procedure successfully eliminated any stress response. Abstract: The Trier Social Stress Test for children (TSST-C) adapted from TSST is one of the most commonly used laboratory paradigms for investigating the effects of stress on cognitive, affective and physiological responses in children and adolescents. Considering that laboratory procedures generate a significant amount of stress to children and adolescents, even in the absence of a stress paradigm, it is important to validate TSST-C against an inactive control condition in which the stress components were absent. Using a randomized design, we tested an inactive control condition, which replaced the TSST-C with a benign video clip (nature scenes viewed while standing), thus removing the stress associated components of the TSST-C. Eighty-eight youth between the ages of 10 and 17 years were randomly assigned to complete the TSST-C or the Inactive Control (IC). Subjective anxiety rating, salivary cortisol, systolic and diastolic blood pressure, and heart rate were collected at eight time points. Subjects in the Inactive Control condition showed no significant changes in blood pressure and heart rate, and decreased anxiety rating and salivary cortisol level throughout the study. Subjects in the stress condition (TSST-C) showed increased anxiety ratings, salivary cortisol, systolic and diastolic blood pressure, and heart rate immediately following TSST-C stress induction. Our findings validated that the TSST-C induced a systemic stress response, and that the Inactive Control can be a promising standardized control condition for the TSST-C and a tool for future psychobiological research. Our results also showed that anxiety reactivity decreased with age while HR reactivity increased with age. Cortisol reactivity did not fall in a linear relationship with age but rather via a quadratic curve, suggesting the mid-age adolescents had the highest cortisol responses to stress compared to their younger and older peers, potentially due to a dual factor of pubertal development and self-control and emotion regulation capacity.